Implementasi Kebijakan Pendidikan (Hakikat, Pendekatan, Strategi, Model, Tahapan, dan Faktor yang Memengaruhi) - Iwan Sanusi; Ade Een Khaeruniah; Siti Aini Latifah Awaliyah (Idarotuna: Jurnal Manajemen Pendidikan Islam, 2024)
This study aims to find out theoretically about the concept of policy implementation in education, because without understanding the concepts and theories at a practical level it will be difficult to achieve the stated policy goals, and the phenomena that occur between expectations and reality are contradictory. This research study uses a qualitative approach based on the literature study. The results of the research are, to achieve the success of the goal of implementing policies in education, it is necessary to pay attention to and understand the concept and meaning of policy implementation, approaches, strategies, models, stages of the process, measurement criteria, and the factors that influence the success of policies in education.